Arkansans' Preferred COVID-19 Testing Locations. (March 2021) - McElfish, Pearl A.; Willis, Don E.; Bryant-Moore, Keneshia; Rojo, Martha O.; Andersen, Jennifer A.; Kaminicki, Kyle F.; James, Laura P.
Introduction: A contributing factor to racial and ethnic disparities during the COVID-19 pandemic may be the accessibility and acceptability of COVID-19 testing. Previous studies found that access to testing has not been equitable across several sociodemographic indicators. This study documents the preferred testing locations and examines differences across sociodemographic factors with a specific focus on race and ethnicity. Methods: This study includes a primary analysis of cross-sectional data using a self-administered digital survey distributed to Arkansas residents using ARresearch, a volunteer research participant registry. The survey had 1288 responses, and 1221 met eligibility criteria for inclusion in the survey. Participants provided sociodemographic information and were asked to select up to 3 preferred testing locations from 12 options. Chi-square tests assessed differences in testing site preference across relevant sociodemographic groups. Results: Participants preferred drive-through clinics as their top location for COVID-19 testing, with 55% reporting this was their preferred method of testing. This pattern was consistent across all comparison groups (ie, age, sex, race/ethnicity, education, insurance status). Significant differences in testing location preference were observed across age, race and ethnicity, and education, with the most differences observed across race and ethnicity. Conclusion: This study reveals that race and ethnicity are important to consider when deciding where to offer COVID-19 testing. The preferences for testing locations among the most vulnerable demographics will be used to develop targeted responses aimed at eliminating disparities in COVID-19 in Arkansas.